When midway won't do: the curvilinear relationship between intrinsic motivation and willingness to be flexible. Issue 2 (25th February 2021) - Solberg, Elizabeth; Lai, Linda; Dysvik, Anders
Abstract : Purpose: Intrinsic motivation is held as critical for employees' willingness to be flexible (WTBF). Yet empirical research suggests that employees who find work intrinsically satisfying could resist work changes. In this study, the authors examine if a curvilinear relationship exists between these variables. Design/methodology/approach: The authors predict that the relationship between intrinsic motivation and employees' WTBF will become more positive as intrinsic motivation advances beyond moderate levels. They examine the role developmental supervisor support plays in generating the critical threshold of intrinsic motivation needed for it to be positively related with WTBF. They test their hypotheses with survey data collected in three substantially different employee samples. Findings: Data support the hypothesized curvilinear relationship between intrinsic motivation and WTBF. Developmental supervisor support is found to influence employee flexibility indirectly through its linear effect on intrinsic motivation and, in turn, the quadratic effect of intrinsic motivation on WTBF. Practical implications: The study provides insight into how and when intrinsic motivation increases employees' WTBF and into the degree of developmental support needed to facilitate a positive relationship between these variables. Originality/value: This is the first study to the author's knowledge that empirically examines the relationship between intrinsic motivation and employees' WTBF.